2021
DOI: 10.1111/jace.17953
|View full text |Cite
|
Sign up to set email alerts
|

Y3NbO7 transparent ceramic series for high refractive index optical lenses

Abstract: A 2 B 2 O 7 and A 3 BO 7 transparent ceramic families are potential materials for optical lenses because of their high refractive index. Although nonstoichiometry is widely present in these material families, its effect on refractive index and optical propertieshas not yet been fully studied. In this study, optical properties are reported for the Y 3 NbO 7 transparent ceramic series, Y 1−x Nb x O 1.5+x (x = 0.20, 0.22, 0.24, 0.25, 0.26), which were fabricated by a pressureless pre-sintering and a hot isostatic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 30 publications
1
3
0
Order By: Relevance
“…The refractive index, n(), was determined using experimental ellipsometry measurements (described in supplementary information Figure SI2). A value of 1.99  0.01 at around 2 µm was obtained, in good agreement with the values reported by Huang et al [21]. The Ho 3+ -doped compound presents a large optical window between 310 nm and 8 m.…”
Section: -Results and Discussionsupporting
confidence: 91%
“…The refractive index, n(), was determined using experimental ellipsometry measurements (described in supplementary information Figure SI2). A value of 1.99  0.01 at around 2 µm was obtained, in good agreement with the values reported by Huang et al [21]. The Ho 3+ -doped compound presents a large optical window between 310 nm and 8 m.…”
Section: -Results and Discussionsupporting
confidence: 91%
“…In addition to zirconate-based ceramics, there is still a high demand for the exploration of new ceramic materials for TBCs. In this case, rare-earth niobates that are widely used as dielectric materials, magnetic materials, protonic ceramic fuel cells (PCFC), and luminescent materials have been considered as new ceramic TBC materials [65][66][67][68][69][70]. As shown in Fig.…”
Section: Rare-earth Niobatesmentioning
confidence: 99%
“…However, Chunlei Wan et al, found that the changing of Re/Nb cation ratio and oxygen ion/vacancy ratio can hardly change the infrared transparency, and consequently, the low emissivity nature of niobates. [7] To improve the emissivity of these thermal barrier ceramics, one would introduce gap-states and lattice distortions into the structures, for example, by incorporating additional rare earth and/or transition metal cations, such as Ce 4+ , Mn 4+ , Ca 2+ , and Cr 3+ . into the host lattice.…”
Section: Introductionmentioning
confidence: 99%
“…However, Chunlei Wan et al., found that the changing of Re/Nb cation ratio and oxygen ion/vacancy ratio can hardly change the infrared transparency, and consequently, the low emissivity nature of niobates. [ 7 ]…”
Section: Introductionmentioning
confidence: 99%